Análise dos Fluxos de Energia para Diferentes Características da Superfície em uma Área Agrícola no Leste da Amazônia - Machado, Wilderclay; Figueira, Antonio; Neto, Furtado; Júnior, Miércio; Tapajós, Raphael; Aguiar, Diego; Silva, Hudson; da Silva, Rodrigo (Ciência e Natura, 2009)
.